Encyclopedia of Pentecostal and charismatic Christianity - Burgess, Stanley M., 1937- (Routledge encyclopedias of religion and society., 2006)
The Encyclopedia of Pentecostal and Charismatic Christianity examines all aspects of the Pentecostal and Charismatic Christianity movements. Focusing on their historical and worldwide development and using a socio-cultural, anthropological approach, this work explains the concepts, practices, and sociology of both movements and analyzes their impact on regional cultures. The Encyclopedia also demonstrates how both movements differ from that of fundamentalism, a movement with strict doctrines that Pentecostalism and Charismatic Christianity are often confused with or mistaken for.